Oncological Safety of Autologous Lipoaspirate Grafting in Breast Cancer Patients: A Systematic Review - Krastev, T. K.; Jonasse, Y.; Kon, M. (Annals of surgical oncology, 2013)
Background Autologous lipoaspirate grafting (ALAG) has become a widely used treatment in breast reconstruction after mastectomy (MST) or breast-conserving treatment (BCT), although there is an ongoing debate about its oncological safety. The aim of this systematic review was to identify, evaluate, and synthesize all clinical evidence examining the oncological risks associated with the procedure. Methods An extensive electronic search was performed in PubMed, Embase, and the Cochrane Library using the keywords “breast” and “autologous lipoaspirate grafting” and synonyms. Results The search yielded a total of 269 unique hits. Twenty clinical trials investigated ALAG in breast reconstruction after cancer. Although nine of them provided oncological follow-up data, only one retrospective cohort and four case series were suitable for analysis. The former reported no significant differences in the locoregional recurrence (LRR) incidence rates between the intervention and control groups for patients with MST as well as BCT. A large multicenter case series reported LRR incidence rates of 1.35 and 2.19 for MST and BCT patients, respectively. The remaining two series were far smaller trials with shorter follow-up and reported no recurrences. No randomized, controlled trials were identified. Most of the available studies consisted of cohorts and case series with short follow-up and no control subjects. Conclusions Although the first reports on cancer recurrence after ALAG are inconclusive, they show promising results. Whether lipoaspirate grafting promotes LRR in breast cancer patients is still unclear. To be able to answer this question, larger prospective trials with longer follow-up are needed.